Materialities of ritual in the Black Atlantic - Ogundiran, Akinwumi; Saunders, Paula (Blacks in the diaspora, 2014)
Focusing on everyday rituals, the essays in this volume look at spheres of social action and the places throughout the Atlantic world where African-descended communities have expressed their values, ideas, beliefs, and spirituality in material terms. The contributors trace the impact of encounters with the Atlantic world on African cultural formation, how entanglement with commerce, commodification, and enslavement and with colonialism, emancipation, and self-rule manifested itself in the shaping of ritual acts such as those associated with birth, death, healing, and protection. Taken as a who
Keywords: African diaspora; Black people : Material culture : Atlantic Ocean Region; Black people : Material culture : Caribbean Area; African Americans : Material culture